Corpus Linguistics and the Analysis of Gendered Language: A Comparative Study of Male and Female Speech Patterns in English - Fayziyev Alisher (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article investigates how corpus linguistics can be used to analyze gendered language differences in English. By examining linguistic patterns exhibited by male and female speakers across various contexts, including formal vs. informal settings, and written vs. spoken language, this study utilizes data from corpora such as the British National Corpus (BNC) and the Corpus of Contemporary American English (COCA). Features such as vocabulary choice, sentence structure, politeness strategies, and discourse markers are explored. The findings reveal that while some linguistic features are strongly gendered, others are more context-dependent. This study also highlights the role of societal norms and cultural expectations in shaping gendered language patterns.